Herpetofauna de Santiago Jalahui, Oaxaca, México - Rendón R, Alejandra; Álvarez, Ticul; Flores Víllela, Oscar (Instituto de Ecología, A.C., 1998)
This study was conducted in the región of Santiago Jalahui, in the northeastern portion of the Mexican State of Oaxaca. Tropical rain forest was the original vegetation in the area, which has been substituted by different secondary plant communities. A total of 282 herpetofaunistic specimens were collected on a monthly basis during 29 effective days of fieid work comprising an annual cycle. Thirty four species were determined, ten amphibians and 24 reptiles. For each species we provide an account of general distribution and morphological characters. This work is the first inventory forthis area. We report for the first time precise localities in the state of Oaxaca for Sphenomorphus assatus assatus, Oxyrhopus petóla sebae and Dryadophis melanolomus veraecrucis, and the second record for Hyla miotympanum. We extend general distribution ranges of Anolis rodríguezi and state distribution of Hemidactylus frenatus and Leptophis mexicanus mexicanus.